Zonasi Sekolah Dalam Upaya Pemerataan Akses Pendidikan : Analisis Keruangan Pada Sebaran Sekolah Menengah Atas di Kota Parepare - Taufiq, Muh; Manaf, Murshal; Alimuddin, Ilham (Urban and Regional Studies Journal, 2023)
Dengan menggunakan pendekatan keruangan (spatial approach) lengkap: 1) Spastial Pattern Analisyst dengan metode Complete Spatial Randomness (CSR) dari tolls Analisyst Nearest network (ANN), 2) Voronoi Analisyst, 3) Breaking Point Analisyst, 4) Service  Area Analisyst, dan 5) Location-Allocation Models, untuk menganalisis kontribusi penerapan sistem zonasi sekolah terhadap pemerataan akses pendidikan secara spasial di Kota Parepare, model spasial zonasi sekolah untuk pemerataan akses pendidikan di Kota Parepare, dan kontribusi zonasi sekolah terhadap pembentukan struktur ruang di Kota Parepare. Sistim Zonasi sekolah berkontribusi positif dalam mendistribusikan responden peserta didik pada wilayah administratifnya dan liputan zonanya masing-masing. Pola random dari distribusi sekolah SMA Negeri di Parepare dengan rerata jarak 1.794,89 meter, pola cluster dari distribsi spasial untuk cluster pemukiman dengan jarak rata-rata 345.7139 Meter, dan pola cluster dari distribusi responden peserta didik SMA dengan jarak rata-rata 113.9075 Meter, menunjukkan adanya equalitas dan opportunitas spasial yang baik, diperkuat dengan mayoritas objek berada pada jangkauan dibawah 3000 Meter dari pusat zona. Secara demografis dan Angka Partisipasi Sekolah, Kota Parepare membutuhkan 2 hingga 4 buah sekolah SMA untuk mengakomodir 12,847 jiwa penduduk usia 15-19 tahun dari data penduduk tahun 2021, sementara kenyataannya Kota Parepare memiliki 31 buah SMA/SMK sederajat, sehingga banyak diantaranya kekurangan peserta didik dan akhirnya tutup. Sementara itu deliniasi zona dengan pertimbangan spatial analisyst complit  dengan Voronoi Analisyst, Breaking Point Analisyst, Service Area Analisyst, dan Location-Alocation model menghasilkan distribusi liputan zona  seluas 1.883.177 M2  untuk zona UPT SMAN 1 Parepare, 46.829.400 M2 untuk zona UPT N 2 Parepare, 31.960.090 M2 untuk zona UPT SMAN 3 Parepare, dan 16.196.590 M2 untuk Zona UPT N 4 Parepare. Sistim zonasi juga berperan terhadap pembentukan struktur ruang di Kota Parepare pada fungsi kegiatan kota terutama pada karakteristtik struktur layanan fasilitas pendidikannya dengan cakupan layanan fasilitas yang terdiri dari 4 pusat zona SMA Negeri yang melayani 13 SMP Negeri, dan 95 sekolah dasar dalam hirarki layanannya. Dalam menghubungkan pusat-pusat layanan dan cluster pemukiman menuju ke pusat zona, struktur jaringan transportasinya menghasilkan 10 koridor rute transportasi untuk perencanaan jaringan transportasi penunjang mobilitas harian pelajar dalam mendukung sistim zonasi sekolah SMA Negeri di Kota Parepare. By using a complete spatial approach: 1) Spatial Pattern Analysis with Complete Spatial Randomness (CSR) method from tolls Analyst Nearest network (ANN), 2) Voronoi Analyst, 3) Breaking Point Analyst, 4) Service Area Analyst, and 5) Location-Allocation Models, to analyze the contribution of the application of the school zoning system to spatial distribution of access to education in Parepare City, school zoning spatial model for equal distribution of access to education in Parepare City, and the contribution of school zoning to the formation of spatial structure in Parepare City. The school zoning system contributes positively in distributing student respondents in their respective administrative area and zoning coverage. The random pattern of the distribution of public senior high school in Parepare with an average distance of 1,794.89 meters, the cluster pattern of spatial distribution for residential clusters with an average distance of 345, 7139 meters, and the cluster pattern of the distribution of respondent to high school student with an average distance of 113, 9075 meters. It indicates the existance of good spatial equality and opportunism, It is reinforced with the majority of objects located at ranges below to 3000 meters from the center of the zone. Demographically and school enrollment rates, Parepare needs 2 to 4 high school to accommodate 12.847 people aged 15 to 19 years from the average population in 2021, while in reality the city of Parepare has 31 senior high school and vocational high school, so that many of them lack students and eventually close. Meanwhile, the delineation of zones with consideration of spatial analysis is complete with Voronoi analysis. Breaking Point Analysis, Service Area Analysis, and Location-Allocation model resulted in a zone coverage distribution of 1,883,177 M2 for the UPT SMAN 1 Parepare zone, 46,829,400 M2 for the UPT N zone 2 Parepare, 31,960,090 M2 for the UPT SMAN 3 Parepare zone, and 16,196,590 M2 for the UPT N 4 Parepare zone. Zoning system also plays a role in the formation of spatial structure in the city of Parepare on the function of urban activity especially in the characteristics of its education facility service structure with a facility service coverage consisting of 4 senior high school zone centers serving 13 public junior high school, and 95 primary school  in the service hierarchy. In connecting service centers and residential cluster to the zone center, the transportation network structure produces 10 transportation route corridors for transportation networking planning to support student’s daily mobility in supporting the zoning system of the senior high school in the city of Parepare